Synergistic effect of corrosion and residual stress on fatigue cracks of finger-type bridge expansion joints. (January 2022) - Yang, Muye; Kainuma, Shigenobu; Nabeshima, Wataru; Yamauchi, Motoshi; Ji, Bohai
Highlights: Corrosion and crack behaviors of FJs serving in highway bridges for more than 25 years were investigated. The residual stress produced by gas cutting was confirmed by cutting method and verified by FEA. Fatigue crack-induced factors were analyzed by clarifying their microstructure, electrochemical properties, and dynamic response. Synergistic effect of corrosion with residual stress led to two main failure modes of different crack-induced mechanisms. Abstract: Finger-type expansion joints (FJs) have been extensively used in highway bridges and are exposed to the repeated impacts of traffic loading and corrosive environments. In this study, the corrosion and cracking behaviors of FJs serving in bridges for more than 25 years were investigated. The microstructure, electrochemical properties, and dynamic response of the FJs were investigated to analyze the fracture mechanism. The results showed that the crack-induced mechanisms of the two main failure modes were different because the synergistic effect of corrosion with residual stress changed depending on the degree of corrosion. First, considerable residual tensile stress, which enhanced the effective stress range, was the critical cause of fatigue crack initiation in the less corroded heat-affected zone (HAZ). Second, the dominant mechanism for cracking was the applied stress to the severely eroded FJ bottom, which was accelerated by galvanic corrosion. Crack-inducing factors included a combination of stress concentration and dynamic springback behavior.